2022
DOI: 10.1002/chem.202203036
|View full text |Cite
|
Sign up to set email alerts
|

A Plausible Prebiotic Path to Nucleosides: Ribosides and Related Aldosides Generated from Ribulose, Fructose, and Similar Abiotic Precursors

Abstract: The prebiotic origins of ribose, nucleosides, and eventually RNA are enduring questions whose answers are central to the RNA world hypothesis. The abiotic synthesis of sugars was first demonstrated over a century ago, but no known prebiotic reaction produces ribose (an aldose sugar) selectively and in good yield. In contrast, ribulose, and fructose (ketose sugars) and other monosaccharides are formed in high yield by several robust abiotic reactions. It is reported here that ketose sugars -both ketopentoses an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 53 publications
0
1
0
Order By: Relevance
“…Their spontaneous reaction with R5P and their pairing properties both suggest that their potential as proto-nucleobases is superior to that of the canonical bases [12,13]. We recently reported that BA sequesters aldoses to form nucleosides from a dynamic, interconverting pool of ketose sugars [15]. The results reported herein extend that discovery by demonstrating the ability of both BA and Mel to form nucleotides in the same reaction, and by demonstrating these putative proto-nucleotides spontaneously form supramolecular assemblies within the crude product mixture of this one-pot reaction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Their spontaneous reaction with R5P and their pairing properties both suggest that their potential as proto-nucleobases is superior to that of the canonical bases [12,13]. We recently reported that BA sequesters aldoses to form nucleosides from a dynamic, interconverting pool of ketose sugars [15]. The results reported herein extend that discovery by demonstrating the ability of both BA and Mel to form nucleotides in the same reaction, and by demonstrating these putative proto-nucleotides spontaneously form supramolecular assemblies within the crude product mixture of this one-pot reaction.…”
Section: Discussionmentioning
confidence: 99%
“…Simply enumerating the chemical space defined by the pyrimidine, purine, and striazine heterocycles with H, NH 2 , and O as exocyclic groups-the class of molecules that potentially existed on the prebiotic Earth along with the canonical nucleobases-reveals 91 molecules from which life could have selected the first base-pairing compounds for a proto-RNA [11]. From these possibilities, previous investigations revealed that barbituric acid (BA), melamine (Mel), and 2,4,6-triaminopyrimidine (TAP) (hereinafter referred to generically as "bases") react with ribose, ribose-5-phosphate (R5P), and other aldose sugars in aqueous solutions to form nucleosides and nucleotides [12][13][14][15] (Figure 1a-c). These putative proto-nucleobases are of further prebiotic interest because both have been synthesized in the same model prebiotic reaction [16], both have good photostability (minimal UV absorbance above 210 nm) [17,18], and both have the ability to assemble as monomers in aqueous solution [19].…”
Section: Introductionmentioning
confidence: 99%
“…There is a large body of evidence to support this claim, including recent work suggesting wet-dry cycling was present during the late Noachian-Hesperian transition 3,4 . Wet-dry cycles have been invoked as potentially important enabling mechanisms for prebiotic chemical evolution due to their ability to concentrate reaction substrates and drive dehydration-condensation reactions, such as drying of sugars and nucleobases to form nucleosides or clay-promoted RNA polymerization [5][6][7][8] . Several missions have identified chemical species on Mars that could support these reactions, such as borates, which stabilize sugars and were identified at Gale Crater by ChemCam 9 , and phyllosilicate clays, which promote RNA polymerization and were identified by the Mars Reconnaissance Orbiter 10 .…”
Section: Introductionmentioning
confidence: 99%
“…There is a large body of evidence to support this claim, including recent work suggesting wet-dry cycling was present during the late Noachian-Hesperian transition 3,4 . Wet-dry cycles have been invoked as potentially important enabling mechanisms for prebiotic chemical evolution due to their ability to concentrate reaction substrates and drive dehydration-condensation reactions, such as drying of sugars and nucleobases to form nucleosides or clay-promoted RNA polymerization [5][6][7][8] . Several missions have identified chemical species on Mars that could support these reactions, such as borates, which stabilize sugars and were identified at Gale Crater by ChemCam 9 , and phyllosilicate clays, which promote RNA polymerization and were identified by the Mars Reconnaissance Orbiter 10 .…”
mentioning
confidence: 99%